PHARMACOTHERAPEUTIC FOLLOW-UP IN A BASIC HEALTH UNIT IN CAÇADOR - SC: CASE STUDY - Sgarbi Aguiar Moriggi, Bruna; Pontes Guedes, Franciele Aparecida; Paloschi de Oliveira, Fernanda; Granemann Nunes, Talita Regina (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Inappropriate use of medications may decrease or exempt the expected therapeutic effect. The objective of this study was to promote pharmacotherapeutic follow-up in a patient with psoriasis under treatment with methotrexate (MTX). The method used was the case study type. The data were collected through consultation, using a structured clinical document and adapted from the Dáder method. During follow-up, misuse of folic acid was identified, which should be administered once a week after administration of MTX, and the patient administered 1 tablet daily until the end of the card. MTX has been shown to interact with hydrochlorothiazide, which may lead to severe leukopenia. The possibility of a severe interaction between MTX and NSAIDs was also observed, a relevant factor since the patient's main complaint was hyperalgesia, a fact that may lead to self-medication and anti-inflammatory use. The data obtained were discussed with the nurse and the doctor of basic health unit, to elaborate the pharmaceutical Intervention. The pharmaceutical intervention allowed correcting the detected problems, as well as stimulating the patient to be able to promote self-care. The importance of the multidisciplinary team in decision-making was perceived during the work.